Tunning of pid controller for coupled-tank liquid levl control system using a stochastic search technique - Mohd. Azam, Nur Syahid (2009)
A common control problem in process industries is the control of fluid and temperature in storage tank, chemical blending and reaction vessel. The situation requires fluid to be supplied to a chemical reactor at a constant rate. An upper tank can be used for filtering the variations in the upstream supply flow. Coupled tanks systems are favorite equipment in control engineering laboratories for research and educational purposes. Although the dynamics of the fluid level control systems are relatively straightforward, sometimes they involve challenging problems. In particular, for tanks where the cross section varies with the fluid level, the dynamics of the flow can change extensively with the operating conditions of the process due to the nonlinearity between level and fluid volume in the tank. In this project, Particle Swarm Optimization (PSO) is used to tuning Proportional-Integral-Derivative (PID) controller parameters for a model of coupled-tank liquid level. The task is to show that PSO tuning method is capable and have better performance in tuning PID parameter. For comparison purpose, conventional tuning method is introduced and analyzed. To measure the performance, performance indices had been used which are ITAE (Integral of Time Absolute Error), IAE (Integral of Absolute Error) and ISE (Integral of Squared of Error). The outcome from this project shows that PSO tuning method have the advantages in reducing the tuning time and can achieved response with satisfactory performance.